Improvement of Myelopoiesis in Cyclophosphamide-Immunosuppressed Mice by Oral Administration of Viable or Non-Viable Lactobacillus Strains - Gramajo Lopez, Andrés; Gutiérrez, Florencia; Saavedra, Lucila; Hebert, Elvira Maria; Alvarez, Susana; Salva, Susana (Frontiers in Immunology, 2021)
Myelosuppression is the major dose-limiting toxicity of cancer chemotherapy. There have been many attempts to find new strategies that reduce myelosuppression. The dietary supplementation with lactic acid bacteria (LAB) improved respiratory innate immune response and the resistance against respiratory pathogens in immunosupressed hosts. Although LAB viability is an important factor in achieving optimal protective effects, non-viable LAB are capable of stimulating immunity. In this work, we studied the ability of oral preventive administration of viable and non-viable Lactobacillus rhamnosus CRL1505 or L. plantarum CRL1506 (Lr05, Lr05NV, Lp06V or Lp06NV, respectively) to minimize myelosuppressive and immunosuppressive effects derived from chemotherapy. Cyclophosphamide (Cy) impaired steady-state myelopoiesis in lactobacilli-treated and untreated control mice. Lr05V, Lr05NV and Lp06V treatments were the most effective to induce the early recovery of bone marrow (BM) tissue architecture, leukocytes, myeloid, pool mitotic and post-mitotic, peroxidase positive, and Gr-1Low/High cells in BM. We selected the CRL1505 strain for being the one capable of maintaining its myelopoiesis-enhancing properties in its non-viable form. Although the CRL1505 treatments do not modify the Cy ability to induce apoptosis, both increased the incorporation of BrdU in BM cells. Consequently, Lr05NV and Lr05V treatments were able to promote early recovery of LSK cells (Lin-Sca-1+c-Kit+ cells), multipotent progenitors (Lin-Sca-1+c-Kit+CD34+ cells), and myeloid cells (Gr-1+Ly6G+Ly6C- cells) with respect to the untreated Cy control. In addition, these treatments were able to increase the frequency of IL17A-producing innate lymphoid cells in the intestinal lamina propria (IL-17A+RORγt+CD4-NKp46+ cells) after Cy injection. These results were correlated with an increase in the IL-17A serum levels, a GM-CSF high expression and a CXCL12 lower expression in BM. Therefore, both Lr05V and Lr05NV treatments are able to activate beneficially the IL-17A/GM-CSF axis and accelerate the recovery of Cy-induced immunosuppression by increasing BM myeloid precursors. We demonstrated for the first time the beneficial effect of CRL1505 strain on myelopoiesis affected by a chemotherapeutic drug. Furthermore, Lr05NV could be a good and safe resource for reducing chemotherapy-induced leukopenia. The results are a starting point for future research and open up broad prospects for future applications of the immunobiotics.